Dor total em pacientes oncológicos em cuidados paliativos: revisão de escopo - Alencar, Mayara Maria Silva da Cruz (2025)
Cicely Saunders, known as the modern founder of the palliative care movement, developed her idea of "total pain." Based on this concept, she placed pain as a fundamental element in health research, as much as the disease itself, and argued that the experience of pain could fluctuate without hierarchies between the physical, mental, social, and spiritual aspects of the patient. People with cancer pain face functional incapacity associated with the disease itself and the pain inherent in it. However, the visible limitations and losses they face affect not only the physical dimension but also the psychological, social, and spiritual dimensions, as well as the work, economic, and even family spheres. The overall objective of this research is to understand, through the literature, how total pain is assessed in adult cancer patients in the context of palliative care. This is a scoping review conducted according to the parameters and recommendations listed by the Joanna Briggs Institute (JBI) and adjusted to the PRISMA Extension Guideline for Scoping Reviews. Based on the Population, Concept, and Context (PCC) strategy proposed by the JBI, where P - Malignant Neoplasms; C - Total Pain; and C - Palliative Care. Therefore, the guiding question of this research was: "How is total pain assessment performed in adult cancer patients undergoing palliative care?" The sources considered were MEDLINE/PubMed, Cochrane Library, LILACS, Web of Science, Scopus, Excerpta Medica dataBASE, and CINAHL, as well as gray literature from secondary sources such as Google Scholar, OpenGray, BDTD, and WHO, as well as ANCP, INCA, ESMO, and ASCO. The sample consisted of 13 publications for analysis. Of the 13 publications, one was from North America (Canada), five from South America (Brazil and Chile), five from Europe (Italy, Poland, the United Kingdom, Denmark, and Germany), and two from Asia (Singapore and India). The discussion was approached through qualitative analysis in thematic categories such as: Multidisciplinary approach to total pain in cancer patients undergoing palliative care; methods for assessing total pain; total pain and its physical, social, psychological, and spiritual dimensions. The conclusion is that a multidisciplinary team is the most effective strategy in the context of "total pain," although its assessment remains fragmented. Interdisciplinary research involving professionals from various health specialties is proposed to enrich the understanding of the phenomenon under study, as well as the development and validation of specific instruments.